New‐onset musicogenic epilepsy after temporal lobe epilepsy surgery. Issue 2 (1st June 2020) - Pejović, Aleksa T.; Vojvodić, Nikola; Djukić, Tijana; Kovačević, Maša; Ristić, Aleksandar J.; Baščarević, Vladimir; Sokić, Dragoslav
ABSTRACT: Musicogenic epilepsy is a reflex epilepsy provoked by listening to or playing music. The epileptogenic network involves temporal regions, usually mesiotemporal structures. We present a 31‐year‐old female patient who experienced musicogenic seizures after a right temporal lobectomy with amygdalohippocampectomy that was performed in order to treat preexisting right mesio‐temporal epilepsy.